Bridging Expectations and Outcomes: A Discrepancy Model Evaluation of Learning Effectiveness in an Islamic Higher Education Context - Usri Usri; Andi Muhammad Ikbal Salam; Muhammad Idris Hasanuddin; Sukri Badaruddin (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study evaluates the effectiveness of the learning process from the perspective of students in the Islamic Religious Education (PAI) Study Program at STAIN Majene, addressing gaps between expectations and actual educational outcomes. A mixed-methods design was used, integrating quantitative data from structured questionnaires and qualitative insights from in-depth interviews. The Discrepancy Evaluation Model guided the analysis to identify inconsistencies between intended and experienced learning processes. Findings reveal significant disparities in four key areas: the relevance of course material, availability of learning resources, instructional methods, and quality of feedback. Students reported that course content often lacks practical application, resources are insufficient or outdated, teaching methods are predominantly traditional, and feedback lacks personalization. To bridge these gaps, the study recommends aligning the curriculum with industry and societal needs, enhancing digital learning resources, training lecturers in interactive and student-centered pedagogies, and providing more individualized feedback. Importantly, involving students in ongoing program evaluations is emphasized as a critical step toward responsive and effective educational reform. Continuous, collaborative improvements are essential to strengthen learning outcomes and graduate competencies. These findings not only inform internal program development at STAIN Majene but also offer valuable insights for similar Islamic education programs seeking to enhance their effectiveness.